Sosialisasi Kampung Iklim di Desa Sembalun Kecamatan Sembalun Kabupaten Lombok Timur - Suryadi; Ibrahim; Adiansyah, Joni Safaat; Nurhayati, Nurhayati; Johari, Harry Irawan; Rakhman, Fathul; Ghazali, Mursal (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Climate change is a global issue that is one of the world’s challenges. Climate change is caused by the increasing concentration of greenhouse gases (GHGs) in the Earth’s atmosphere. One contributor to GHGs is the decomposition of waste, which commonly produces methane gas (CH₄). Waste management is a problem faced by our partner in Sembalun Village, Sembalun Subdistrict, East Lombok Regency. On the other hand, the government, through the Ministry of Environment and Forestry (KLHK), issued regulation P.68/2016 regarding Climate Villages. The purpose of this community service is to provide an understanding of climate villages to the community in Sembalun Village, Sembalun Subdistrict, East Lombok Regency. The steps in implementing this community service include: 1) identifying target groups/partners, 2) conducting a Focus Group Discussion (FGD) involving relevant stakeholders, and 3) field visits to waste disposal facilities. The outcome of this activity is the establishment of Climate Village Program (Proklim) coordinators and technical improvements in waste management, particularly in landfill operations